2017
DOI: 10.1002/ejhf.796
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial expression of Toll‐like receptor 4 predicts the response to immunosuppressive therapy in patients with virus‐negative chronic inflammatory cardiomyopathy

Abstract: TLR4 is highly expressed in human myocarditis responding to immunosuppression. It can be considered as a new sensitive marker in patient selection predicting a good response to immunosuppressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 30 publications
0
27
0
1
Order By: Relevance
“…Although a broader use to improve the diagnosis of myocarditis and inflammatory cardiomyopathy has recently been proposed, many statements reserved the indications to endomyocardial biopsy for selected cases . In a patient with newly diagnosed DCM, endomyocardial biopsy is reasonable when there is a high probability of a specific diagnosis which can be confirmed only in myocardial samples and is amenable to therapy that has the potential to change the course of the disease . Examples of such scenarios include active myocarditis ( Figure ), the contemporary presence of a hypertrophic and dilated left ventricle (for example in end‐stage hypertrophic cardiomyopathy), cardiac amyloidosis, sarcoidosis, or haemochromatosis …”
Section: Specific Aspects In the Clinical Management Of Dilated Cardimentioning
confidence: 99%
“…Although a broader use to improve the diagnosis of myocarditis and inflammatory cardiomyopathy has recently been proposed, many statements reserved the indications to endomyocardial biopsy for selected cases . In a patient with newly diagnosed DCM, endomyocardial biopsy is reasonable when there is a high probability of a specific diagnosis which can be confirmed only in myocardial samples and is amenable to therapy that has the potential to change the course of the disease . Examples of such scenarios include active myocarditis ( Figure ), the contemporary presence of a hypertrophic and dilated left ventricle (for example in end‐stage hypertrophic cardiomyopathy), cardiac amyloidosis, sarcoidosis, or haemochromatosis …”
Section: Specific Aspects In the Clinical Management Of Dilated Cardimentioning
confidence: 99%
“…Heart tissue samples were treated as described [11]. The expression of myocardial aldosterone receptors and Aquaporin 1 and 4 was visualized by using mineralocorticoid receptor monoclonal antibody (1:500), anti-Aqp1 (1:100) and anti-Aqp4 (1: 200).…”
Section: Protein Isolation and Western Blotmentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4), the first described member of the TLR family, mediates the inflammatory response in the myocardium; in addition, its mediated inflammatory signaling pathway plays a key role in myocarditis, myocardial infarction, and ischemia-reperfusion injury [7][8][9]. Multiple studies have demonstrated that TLR4/MyD88/NF-κB signaling controls the production of proinflammatory factors and induces the inflammatory response in the myocardial tissues, which is the main cause of myocardial tissue injury [10,11].…”
Section: Introductionmentioning
confidence: 99%